Manajemen pembelajaran matematika dalam implementasi kurikulum merdeka: studi kasus di SMPN 4 Samarinda - Subaer, Sukma; Fendiyanto, Petrus (Universitas PGRI Semarang, 2025)
This study aimed to determine how mathematics teachers manage and organize learning, as well as problems and obstacles in implementing an independent curriculum in class VIII of SMPN 4 Samarinda. This study is qualitative and uses a case study. Interviews, observations, and documentation are data collection methods. The subjects of this study were mathematics teachers in class VIII of SMPN 4 Samarinda, as well as the Deputy Head of Curriculum and student representatives in class VIII. Data analysis includes reduction, presentation, and conclusion. The study results indicate that mathematics teachers in class VIII of SMPN 4 Samarinda carry out the learning management process quite well, which includes planning, organizing, implementing, evaluating, and assessing learning. However, the process is not yet fully optimal. It is difficult for teachers to manage time.